Under-ice respiration rates shift the annual carbon cycle in the mixed layer of an oligotrophic lake from autotrophy to heterotrophy. Issue 1 (2nd January 2021) - Brentrup, Jennifer A.; Richardson, David C.; Carey, Cayelan C.; Ward, Nicole K.; Bruesewitz, Denise A.; Weathers, Kathleen C.
ABSTRACT: Ecosystem metabolism is an integrative measure of the production and respiration of carbon in aquatic ecosystems. However, under-ice regions and mixing periods are infrequently sampled because of logistical challenges and assumptions of low biological activity, resulting in limited understanding of the contribution of winter epilimnetic metabolism to annual carbon cycling. Aquatic ecosystems can emit up to 76% of the carbon they receive from terrestrial landscapes as carbon dioxide to the atmosphere, making them significant contributors to Earth's carbon cycle. Consequently, studying metabolism under ice is especially important given that warmer winters have already shortened ice cover and lengthened ice transitional periods, potentially resulting in greater carbon dioxide emissions. Using a continuous year of epilimnetic high-frequency dissolved oxygen data, we found that gross primary production was low but not absent under ice and increased during the end of the under-ice period. Despite cold water temperatures, under-ice respiration was 1.2 times higher than summer respiration, and ice-on and ice-off periods were important contributors to annual metabolism estimates. On average, under-ice net ecosystem production (NEP) was negative, in contrast to positive NEP for the spring and summer periods. Including winter metabolism estimates flipped annual NEP from autotrophy to heterotrophy, demonstrating that year-round sampling is essential for accurately assessing carbon cycling in lakes.